“Can’t you just tell me how to do this?” Students’ attitudes through the eyes of lecturers - Sigurðardóttir, Margrét Sigrún; Heijstra, Thamar Melanie (Menntavísindasvið Háskóla Íslands, 2016)
Changes have taken place within the university, not least with regard to teaching methods. Apart from an increase in the number of students, they also have a more diverse background than before. This makes teaching more challenging and calls for new teaching methods. This article discusses the case of a qualitative research course taught in the autumn of 2014 at the Faculty of Business Administration at the University of Iceland. This is a course with over 130 students in which the teachers have started to use the flip-teaching method, where students listen to a lecture at home and come to the university for a weekly discussion lesson. The class of 2014 was split into five discussion groups, and each one was taught identical material. Early in the semester the teachers started noticing a difference between the groups. However, they were unable to pinpoint what this difference entailed, exactly. The main research question put forward in this article is, therefore: How can teachers better live up to the needs of different groups of students with regard to the build-up and implemention of the course? To be able to answer this research question it was necessary to gain a better insight into the subquestion: Why are there different attitudes between the student groups? To be able to answer these questions, the teachers wrote down their impressions of each group on a weekly basis and students were asked to fill out a survey about different types of learning approaches. They also examined the mid-semester teaching survey outcomes. The analysis revealed three themes: insecurity among students, demanding teaching from the perspective of the teachers, and student learning approaches. Some students seemed uncomfortable with the way in which qualitative research methods were taught, causing feelings of insecurity among them; they wanted more standard descriptions on how to conduct interviews, on how to analyse data, or on how many codes they were supposed to identify. Some groups were sensitive to any critique on their ...